The Role of Endoplasmic Reticulum Aminopeptidase 1 Biology in Immune Evasion by Tumours - Emma Reeves; Edward James (Journal of Vaccines and Immunology - Peertechz Publications, 2015)
Expression of MHC I at the cell surface is essential for presenting peptides to circulating cytotoxic T cells. Interference with a number of components of the antigen processing machinery is an immune evasion mechanism that has been highlighted in a number of malignancies. Endoplasmic reticulum aminopeptidase 1 (ERAP1), a key component of the antigen processing pathway, undertakes the final N-terminal processing of peptide epitopes for MHC I presentation. ERAP1 acts to regulate and define the repertoire of peptides at the cell surface; changes in ERAP1 activity have significant consequences on CD8+ T cell and NK cell responses. Single nucleotide polymorphisms (SNPs) in ERAP1 have been strongly associated with a number of autoimmune conditions, viral infections and cancer. The resence of SNPs in ERAP1 significantly alter the ability to generate stable peptide epitopes for presentation, thereby altering the peptidome and subsequent immune response. Interestingly, ERAP1 variants have been significantly associated with prognosis and survival in virally induced cancer. Here we discuss the emerging role of ERAP1 activity in malignancy, and the contribution of ERAP1 SNP variants in the generation or destruction of epitopes in tumour cells. This potential immune evasion strategy employed by a number of tumour cells may therefore predispose individuals to cancer based on their ability to generate the required epitopes and form adequate immune response.